Employee noise exposure and octave band analysis in a manufacturing setting - Gieseck, Darren, author; Brazile, William, advisor; Autenrieth, Daniel, committee member; Gutilla, Margaret, committee member (Colorado State University. Libraries, 2023)
Worker exposure to hazardous levels of noise continues to be a concern in United States (US) industries. The National Institute for Occupational Safety and Health has estimated that twenty-two million US workers are exposed to hazardous levels of noise each year, increasing the risk for noise-induced hearing loss (NIHL). One industry sector of concern for worker exposure to noise is metal can manufacturing because of the types and number of machines used in the production areas. To help further characterize the risk NIHL in the metal can manufacturing sector, a comprehensive noise evaluation was performed at a manufacturing site that produced aluminum metal cans. The purpose of this study was to (1) determine if workers in a metal can manufacturing facility were overexposed to hazardous levels of noise that could potentially result in NIHL; (2) determine the machinery frequencies greater than 85 dBC to which employees were exposed; and (3) provide sound mitigation recommendations to the facility's safety team. Area noise levels were collected with a sound level meter (SLM) and personal noise samples were taken using wearable noise dosimeters. 30 production employees participated in sampling over the course of five days and their measured work shift noise exposures were compared to published occupational exposure limits to determine if they were at increased risk of hearing loss. Personal noise exposures were compared to the Occupational Safety and Health Administration's (OSHA) noise Action Level (AL) and Permissible Exposure Limit (PEL); the American Conference of Governmental Industrial Hygienists' (ACGIH) Threshold Limit Value (TLV); and the National Institute for Occupational Safety and Health's (NIOSH) Recommended Exposure Level (REL). Of the 30 employees sampled, 100% exceeded the OSHA AL, 100% exceeded the OSHA PEL, and 100% exceeded the NIOSH REL/ACGIH TLV. To provide statistical support of these findings, a 95% confidence interval was calculated for each occupational exposure standard along with upper and lower prediction limits. Additionally, the frequencies greater than 85 dBC obtained from the area noise samples associated with the production machinery ranged from 63 Hz – 6,300 Hz with noise levels that ranged from 97.1 dBC – 99.6 dBC and Z-weighted frequencies greater than 85 dB ranged from 32 Hz – 8,000 Hz. From these findings, noise mitigation recommendations were provided that were focused on establishing hearing attenuation to 80 dBA. This involved ongoing fit testing of hearing protection for employees, training, and addressing the specific frequencies associated with each machine type.